2009
DOI: 10.1104/pp.109.137935
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Chromosomal Evidence for Allopolyploidy in Soybean  

Abstract: Recent studies have documented that the soybean (Glycine max) genome has undergone two rounds of large-scale genome and/or segmental duplication. To shed light on the timing and nature of these duplication events, we characterized and analyzed two subfamilies of high-copy centromeric satellite repeats, CentGm-1 and CentGm-2, using a combination of computational and molecular cytogenetic approaches. These two subfamilies of satellite repeats mark distinct subsets of soybean centromeres and, in at least one case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
170
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 144 publications
(189 citation statements)
references
References 56 publications
(68 reference statements)
14
170
1
4
Order By: Relevance
“…The ancestor of genus Glycine was coincident with a polyploidization event 5 to 10 MYA (Doyle and Egan, 2010). Furthermore, observations at molecular and chromosomal levels support the hypothesis that the recent tetraploid event was allopolyploidy and the putative ancestral diploid genomes of soybean are extinct (Gill et al, 2009). Soybean differs from some paleopolyploid genomes in that it has been diploidized (disomic pairing), but the level of genetic collinearity between duplicated segments is much higher than seen in maize, which had a roughly contemporaneous duplication event Innes et al, 2008;Van et al, 2008).…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…The ancestor of genus Glycine was coincident with a polyploidization event 5 to 10 MYA (Doyle and Egan, 2010). Furthermore, observations at molecular and chromosomal levels support the hypothesis that the recent tetraploid event was allopolyploidy and the putative ancestral diploid genomes of soybean are extinct (Gill et al, 2009). Soybean differs from some paleopolyploid genomes in that it has been diploidized (disomic pairing), but the level of genetic collinearity between duplicated segments is much higher than seen in maize, which had a roughly contemporaneous duplication event Innes et al, 2008;Van et al, 2008).…”
Section: Introductionsupporting
confidence: 58%
“…Previous studies have shown that a recent genome duplication in soybean occurring ;13 MYA was correlated with the distribution of Ks ranging from 0.03 to ;0.39 (Schlueter et al, 2004;Shoemaker et al, 2006;Schmutz et al, 2010). Because the distribution of Ks between Gm8 and Gm15 in this study located within the range of the distribution of Ks from the recent genome duplication in soybean, we concluded that the divergence time for Gm8 and Gm15, 13 million years, precedes the polyploidization event ;5 to 10 MYA (Doyle and Egan, 2010;Gill et al, 2009). …”
Section: Synonymous Substitution Rates Are Biased To Gm8mentioning
confidence: 55%
See 3 more Smart Citations